The water circulation in Kavala Bay (North Aegean) - KARDARAS, TH. (Mediterranean Marine Science, 2005)
In this work an attempt is made to explain a case of the water circulation in the North Aegean shelf based on a set of oceanographic and meteorological measurements. It is argued that hydrodynamic conditions created by the meteorological fields of surface wind and pressure, force the renewal of the waters in the coastal area of Kavala Bay. It is shown that, although the mean horizontal water velocity is estimated at about 7cm/sec providing a time period of water renewal of the bay at about 4 days, the geostrophic circulation of the wider area in the North Aegean, controlled by the geometry of the local area, accelerates the water movement in the bay decreasing the time required for the renewal to less than one day.